Dialog Antar-Agama dengan Imersion: Dari Perjumpaan Menuju Kerja Bersama - Widiyono, A. Nugraha (Jurnal Orientasi Baru, 2006)
This article is presented based on immersion experience during workshop on inter-cultural and inter-religious dialogue run by Jesuit School of Theology of Berkeley and Sanata Dharma University of Yogyakarta on January 8th-22nd, 2006 in Yogyakarta. Encountering people from different cultural and religious background purifies our understanding about